Rapid and easy quantitative identification of Cronobacter spp. in infant formula milk powder by isothermal strand-exchange-amplification based molecular capturing lateral flow strip. (August 2021) - Gao, Yan; Ye, Yingwang; Xu, Jianguo; Wu, Qian; Yao, Bangben; Chen, Wei
Abstract: Food-borne pathogen detection is of great significance for guaranteeing food safety and human health. Herein, we have developed a new detection method for rapid and easy quantitative identification of Cronobacter spp . in infant formula milk powder. This method well couples the advantages of isothermal strand exchange amplification (SEA) and molecular capturing lateral flow strip (LFS). The presence of Cronobacter spp . DNA template can be isothermally and exponentially amplified by SEA with a pair of labeled functional primers without thermal controller device. The high amplification efficiency of SEA enables the accumulation of plentiful dual-labeled amplicons that can be captured by a molecular capturing LFS with the using of fluorescent microsphere (FM) as tagger, which can be excited at 365 nm and the signal at 625 nm can be acquired for the quantitative analysis. The Cronobacter spp . in the concentration from 10 1 to 10 6  cfu/mL can be accurately determined with the visual detection limit of 10 cfu/mL within less than 1 h even in the complex infant formula milk powder. We expect this unique SEA-LFS method with its favorable assay performance can be a powerful analytical protocol in the field of foodborne pathogen detection. Highlights: Sequence exchange amplification is constructed for genetic detection of Cronobacter . Fluorescent lateral flow strip is developed for easy visual analysis of SEA products. SEA-LFS method is applied for rapid Cronobacter detection in infant powder. SEA-LFS can be performed without any expensive instruments for on-site analysis.